Electrosynthesis of Nitrate via the Oxidation of Nitrogen on Tensile‐Strained Palladium Porous Nanosheets. Issue 9 (7th January 2021) - Han, Shuhe; Wang, Changhong; Wang, Yuting; Yu, Yifu; Zhang, Bin
Abstract: Nitrate is one of the essential raw ingredients in agriculture and industry. The electrochemical nitrogen oxidation reaction (NOR) is promising to replace the conventional nitrate synthesis industry with high energy consumption and greenhouse gas emission. Here, tensile‐strained palladium porous nanosheets (Pd‐s PNSs) were prepared. They exhibited enhanced activity for electrochemical NOR at ambient conditions, greatly outperforming Pd nanosheets. 15 N isotope labeling experiments proved that nitrate originated from nitrogen oxidation. Combining electrochemical in situ Raman and FTIR spectroscopy with density functional calculations, it was revealed that the tensile strain could facilitate the formation of NOR active species of PdO2, leading to high activity. Abstract : Tensile‐strained palladium porous nanosheets exhibited enhanced activity for nitrogen electrooxidation to nitrate at ambient conditions. 15 N isotope labeling experiments showed that nitrate originated from nitrogen electrooxidation. Electrochemical in situ characterizations and theoretical simulation revealed that the tensile strain could facilitate the formation of PdO2 active species and lead to high activity.